2022
DOI: 10.1007/s10815-022-02658-y
|View full text |Cite
|
Sign up to set email alerts
|

Low BMI is associated with poor IUI outcomes: a retrospective study in 13,745 cycles

Abstract: Background: Although the effect of body mass index (BMI) on the outcome of in vitro fertilization (IVF) has been extensively studied, its correlation with intrauterine insemination (IUI) has rarely been reported. Therefore, we aimed to examine the impact of BMI on IUI outcomes Methods: Six thousand four hundred and seven women undergoing 13,745 IUI cycles strati ed by BMI were included in the study. Cox regression was used to analyze the association between BMI and cumulative live birth across multiple IUI cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…36 In addition, there are some studies that show no relationship between endometrial thickness and pregnancy after IUI. 37,38 In addition, Amerigo Vitagliano et al found that endometrial scratch injury was associated with a higher clinical pregnancy rate of IUI cycles. 39 Therefore, it is necessary to consider "endometrial factor" in the process of IUI.…”
Section: Discussionmentioning
confidence: 99%
“…36 In addition, there are some studies that show no relationship between endometrial thickness and pregnancy after IUI. 37,38 In addition, Amerigo Vitagliano et al found that endometrial scratch injury was associated with a higher clinical pregnancy rate of IUI cycles. 39 Therefore, it is necessary to consider "endometrial factor" in the process of IUI.…”
Section: Discussionmentioning
confidence: 99%
“…This can have a dual impact on ovarian function and endometrial development, ultimately affecting the pregnancy outcome of IUI [ 16 ]. Research has shown that women with relatively low BMI have lower concentrations of serum hCG and progesterone, which can affect endometrial thickness and lead to early pregnancy loss [ 17 ]. Studies have also found that being underweight is associated with infertility due to anovulation and hypothalamic amenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Aydin et al [ 27 ] showed that BMI was negatively associated with pregnancies in the first OS IUI cycle. Zheng et al [ 28 ] showed that low BMI was associated with a lower per-cycle LBR of IUI. Besides, Whynott et al [ 29 ] concluded that overweight or obesity does not appear to have a negative effect on live birth after IUI, but obesity may be associated with a higher risk of biochemical pregnancy after IUI.…”
Section: Discussionmentioning
confidence: 99%